Penggunaan Model Make A Match Meningkatkan Motivasi Dan Hasil Belajar Bilangan Kuadrat Siswa Kelas V SDN 4 Pare Tahun Pelajaran 2019/2020 - Else Yuniasih (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
In the process of learning mathematics, the low score is because students do not have the interest and motivation to learn mathematics. The purpose of this study was to increase motivation and learning outcomes of quadratic numbers in fifth grade students of SDN 4 Pare in the 2019/2020 academic year with the Make a Match learning model. This research is a quantitative research with correlational method. Sampling using observation and tests. The results showed that the average student motivation in the initial condition was 60%, the first cycle was 71.43% and in the second cycle it was 85.71%. The results of the square number in the initial conditions mean the value of 60 classical completeness level 57. In the first cycle, the average value of 70 classical completeness level is 71. In the second cycle, the average value is 85.71 classical completeness level is 85. Based on the actions taken, it can be concluded that the use of the learning model Make a Match increases the motivation of fifth graders at SDN 4 Pare for the 2019/2020 academic year by 26.14% and increases the learning outcomes of quadratic numbers by 28%.